Analisis tata letak Ruang Produksi Rumah Kedelai Soya Ayu melalui metode Activity Relationship Chart (ARC) dan Total Closeness Rating (TCR) - Sukandar, Kansha Amanda Prasyawalli; Safira, Salma; Rizkiana, Aura Selly; Sukirman, Selfiani; Prabowo, Alika Renisha Putri (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Rumah Kedelai Soya Ayu focuses on the production and sale of various soy-based products. The business offers high-quality soy milk as a result of the creativity and dedication of Agus Murtini, who started the business in 2019 with a focus on quality and innovation. In this study, Rumah Kedelai Soya Ayu was selected as the research site to evaluate the effectiveness of its facility layout and product display within a constrained spatial environment. The aim was to optimize the use of limited space. The research aims to evaluate the flow of activities between facilities using the Activity Relationship Chart (ARC) and Total Closeness Rating (TCR) methods. The results show that the soy milk production area should be prioritized as it has the highest TCR value of 190, making it important to place other facilities, such as storage rooms and display areas, in close proximity to improve operational efficiency. A good layout strategy at Rumah Kedelai Soya Ayu not only facilitates operations but also enhances the customer experience. Customers can easily enjoy high-quality products, creating a pleasant shopping environment.